Diaphragm and its preparation method and application

By using flavonoids in the battery separator, metal ions are prevented from deposition on the surface of the negative electrode sheet, the problems of battery capacity loss and short circuit are solved, and the circulation performance and safety of the battery are improved.

CN119764754APending Publication Date: 2025-04-04CHONGQING FUDI BATTERY RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410704332.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-31
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

During the long-term use of the battery, metal ions in the positive electrode active material are dissolved and transferred, causing side reactions to occur, destroying the electrolyte membrane, causing battery capacity loss and short circuit.

Method used

Using a separator with flavonoids, the flavonoids are complexed with metal ions dissolved from the positive electrode sheet to prevent metal ions from depositing on the surface of the negative electrode sheet.

Benefits of technology

Improves the cycle performance and safety of the battery, reduces the battery impedance, and extends the battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764754A_ABST
    Figure CN119764754A_ABST
Patent Text Reader

Abstract

The present application provides a diaphragm and a preparation method and application thereof, wherein the diaphragm comprises a base film and a coating disposed on at least one side of the base film, wherein the coating comprises a flavonoid compound. The diaphragm provided in the present application comprises a coating comprising a flavonoid compound, which can inhibit metal ion deposition and is beneficial to improving the cycle performance and safety performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and in particular to a diaphragm and a preparation method and application thereof. Background Art

[0002] At present, during long-term use of batteries, metal ions (such as iron, nickel and manganese) in the positive electrode active material will dissolve and transfer, and deposit on the surface of the negative electrode, causing side reactions, destroying the electrolyte membrane, causing battery capacity loss, and even battery short circuit. In the related art, a large amount of vinylene carbonate can be added to the electrolyte, which is conducive to the formation of a new electrolyte membrane, preventing metal deposition, and reducing the adverse effects of metal deposition; however, during long-term cyclic use, vinylene carbonate will form a highly dense electrolyte membrane on the surface of the negative electrode, increasing the battery impedance, resulting in a decrease in battery power and cycle performance. Therefore, it is necessary to provide a solution that can inhibit metal deposition, reduce battery impedance, and improve battery safety. Summary of the invention

[0003] In view of this, the present application provides a diaphragm and a preparation method and application thereof. The diaphragm includes a coating having flavonoid compounds. The flavonoid compounds can undergo a complex reaction with metal ions dissolved from the positive electrode plate to prevent the metal ions from being deposited on the surface of the negative electrode plate, which is beneficial to improving the cycle performance and safety of the battery.

[0004] In a first aspect, the present application provides a membrane, comprising a base membrane and a coating disposed on at least one surface of the base membrane, wherein the coating comprises a flavonoid compound.

[0005] Optionally, based on the mass of the flavonoid compound, the coating surface density of the coating on the surface of the diaphragm is 0.05 g / m 2 -0.5g / m 2 .

[0006] Optionally, in the membrane, the mass percentage of the flavonoid compound is 1%-6%.

[0007] Optionally, the flavonoids include one or more of flavones, flavonols, dihydroflavones, dihydroflavonols, isoflavones, dihydroisoflavones, chalcones, dihydrochalcones, aurone, anthocyanidins, rutin, and catechins.

[0008] Optionally, the flavonoid compound includes anthocyanidin, and the structural formula of the flavonoid compound is Among them, the R 1 and the R 2 are independently -H, -OH and -OCH 3 One of the R 3 is -H or a glycosyl group, the R4 It is -OH or sugar group.

[0009] Optionally, the material of the base film includes one or more of polyethylene, polypropylene, polyvinylidene fluoride and polyimide.

[0010] Optionally, the coating further comprises a binder, and the binder comprises one or more of polyvinylidene fluoride, polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, polystyrene, polybutadiene, acrylic resin, epoxy resin, polyethylene oxide, sodium carboxymethyl cellulose and styrene-butadiene latex.

[0011] Optionally, in the coating, the mass ratio of the binder to the flavonoid compound is (0.01-1):1.

[0012] The diaphragm provided in the present application includes a coating layer having flavonoid compounds, which can react with dissolved metal ions to form a complex, thereby preventing metal from being deposited on the negative electrode plate and improving the cycle performance and safety of the battery.

[0013] In a second aspect, the present application provides a method for preparing a diaphragm, comprising:

[0014] dissolving the flavonoid compound in a solvent to obtain a coating slurry;

[0015] The coating slurry is coated on a base film and dried to obtain a separator.

[0016] Optionally, the solvent includes a non-polar organic solvent.

[0017] Optionally, the non-polar organic solvent includes one or more of diethyl ether, dioxane, and benzene.

[0018] Optionally, the drying temperature is 50°C-100°C, and the drying time is 1 min-50 min.

[0019] The preparation method of the diaphragm provided in the present application is novel, the preparation process is simple, and the prepared product has excellent performance.

[0020] In a third aspect, the present application provides a battery comprising a positive electrode plate, a negative electrode plate, and a diaphragm and an electrolyte arranged between the positive electrode plate and the negative electrode plate, wherein the diaphragm comprises the diaphragm described in the first aspect or the diaphragm prepared by the preparation method described in the second aspect.

[0021] Optionally, the positive electrode plate includes a positive electrode active material, and the positive electrode active material includes one or more of a lithium iron phosphate material, a lithium iron manganese phosphate material, a lithium manganese oxide material, a nickel cobalt manganese material, and a nickel cobalt aluminum material.

[0022] Optionally, the electrolyte includes an electrolyte salt, an additive and an electrolyte solvent.

[0023] Optionally, the electrolyte solvent includes one or more of ethylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, polycarbonate, ethyl propionate and ethyl acetate.

[0024] Optionally, the additive includes one or more of vinylene carbonate, triphenyl phosphate, methylene methanedisulfonate and vinyl sulfate.

[0025] Optionally, the additive includes vinylene carbonate, and the additive includes vinylene carbonate, and the mass percentage of the flavonoid compound in the diaphragm is defined as a%, and the mass percentage of the vinylene carbonate in the electrolyte is defined as b%, satisfying a / 2+b≥3.

[0026] The battery provided in the present application includes a diaphragm having a flavonoid compound coating, which can inhibit metal deposition, improve battery capacity and cycle performance, reduce battery impedance, and improve battery safety.

[0027] In a fourth aspect, the present application provides an electrical device, wherein the electrical device comprises the battery described in the third aspect.

[0028] The electrical equipment provided by this application has a long service life, high safety performance and strong product competitiveness. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the embodiments or the prior art description. The specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.

[0030] Figure 1 A schematic diagram of the cross-sectional structure of a diaphragm provided in one embodiment of the present application;

[0031] Figure 2 A schematic diagram of the cross-sectional structure of a battery provided in one embodiment of the present application. DETAILED DESCRIPTION

[0032] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0033] See also Figure 1, is a schematic diagram of the cross-sectional structure of a diaphragm provided in one embodiment of the present application, wherein the diaphragm 100 comprises a base film 11 and a coating 12 disposed on at least one side of the base film 11, wherein the coating 12 comprises a flavonoid compound. In the present application, the diaphragm coating comprises a flavonoid compound, and when used in a battery, the flavonoid compound can react with metal ions (such as iron, manganese and nickel, etc.) other than lithium ions dissolved from the positive electrode plate to form a structurally stable flavonoid compound-metal complex, which effectively prevents the metal ions from being deposited on the surface of the negative electrode plate without preventing the migration of lithium ions, thereby improving the cycle performance and safety performance of the battery; moreover, when the diaphragm is used in a battery system in which the electrolyte comprises vinylene carbonate, the flavonoid compound in the diaphragm coating can synergize with vinylene carbonate to jointly reduce the adverse effects of metal ion deposition, while reducing the battery impedance, increasing the battery capacity and power, and solving the problem that the use of vinylene carbonate in the electrolyte is not conducive to reducing the internal resistance of the battery. The diaphragm provided in the present application is conducive to improving the cycle life of the battery, and improving the electrochemical performance and safety of the battery.

[0034] In the present application, the base film can improve the mechanical strength of the diaphragm 100 and extend the service life of the diaphragm 100. Specifically, the material of the base film 11 can be, but is not limited to, one or more of polyethylene, polypropylene, polyvinylidene fluoride and polyimide. In one embodiment of the present application, the material of the base film 11 can be polyethylene. In another embodiment of the present application, the material of the base film 11 can be a composite diaphragm of polyethylene and polypropylene.

[0035] In one embodiment of the present application, the thickness of the base film 11 is 7 μm-20 μm. The appropriate thickness of the base film 11 can maintain high mechanical strength while improving the conductivity of the separator 100 and the electrochemical performance of the battery. Specifically, the thickness of the base film 11 can be, but not limited to, 7 μm, 10 μm, 12 μm, 15 μm, 18 μm or 20 μm, etc. In one embodiment of the present application, the thickness of the base film 11 can be 7 μm-15 μm. In another embodiment of the present application, the thickness of the base film 11 can be, but not limited to, 10 μm-20 μm.

[0036] In one embodiment of the present application, the surface density of the base film 11 is 3 g / m 2 -20g / m 2 Specifically, the surface density of the base film can be, but is not limited to, 3 g / m 2 , 5g / m 2 , 8g / m 2 , 10g / m 2 , 15g / m 2 , 18g / m 2 or 3g / m 2 In one embodiment of the present application, the surface density of the base film can be 3g / m 2-15g / m 2 In another embodiment of the present application, the surface density of the base film can be 10 g / m 2 -20g / m 2 .

[0037] In an embodiment of the present application, the base film 11 has a coating 12 on at least one side of the surface. In some embodiments, both sides of the base film 11 have a coating 12; in some embodiments, the base film 11 has a coating 12 only on one side close to the positive electrode; in some embodiments, the base film 11 has a coating 12 only on a layer close to the negative electrode. In an embodiment of the present application, the coating 12 is disposed on one side of the base film 11 close to the positive electrode, which can shorten the diffusion path of metal ions, accelerate the reaction of metal ions with flavonoid compounds, reduce the adverse effects of metal ion deposition, and improve the electrochemical performance of the battery.

[0038] In one embodiment of the present application, the flavonoid compound has low solubility in the electrolyte. When applied to the battery separator, it can effectively complex the metal ions (such as iron, manganese and nickel, etc.) dissolved from the positive electrode plate except lithium ions. At the same time, the complex product generated can be stabilized on the separator, with low solubility, which can increase the battery cycle life. Specifically, the flavonoid compound can include but is not limited to one or more of flavones, flavonols, dihydroflavones, dihydroflavonols, isoflavones, dihydroisoflavones, chalcones, dihydrochalcones, aurone, anthocyanidins, rutin, and catechins. In one embodiment of the present application, the flavonoid compound can be flavones.

[0039] In one embodiment of the present application, the coating 12 includes anthocyanin, and the structural formula of anthocyanin is Among them, R 1 and R 2 are independently -H, -OH and -OCH 3 One of them, R 3 is -H or sugar group, R 4 Anthocyanins can bind to metal ions, prevent them from depositing on the surface of the negative electrode, and improve the capacity and safety of the battery. Anthocyanins have certain antioxidant properties, which can alleviate the side reactions of the positive electrode, thereby reducing the generation of acidic gases and further increasing the cycle life of the battery. In addition, the color of anthocyanins changes with the pH value, which can be used to identify the acidic gases generated by the side reactions of the positive electrode to predict the service life of the battery.

[0040] In one embodiment of the present application, the coating 12 also includes a binder, which can improve the bonding force of the coating 12, improve the structural reliability of the diaphragm 100, and improve the electrochemical performance of the diaphragm 100. Specifically, the binder can be, but is not limited to, one or more of polyvinylidene fluoride, polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, polystyrene, polybutadiene, acrylic resin, epoxy resin, polyethylene oxide, sodium carboxymethyl cellulose and styrene-butadiene latex. In one embodiment of the present application, the binder in the coating 12 can be polyvinylidene fluoride. In another embodiment of the present application, the binder in the coating 12 can be sodium carboxymethyl cellulose.

[0041] In one embodiment of the present application, in the coating, the mass ratio of the binder to the flavonoid compound is (0.01-1):1, which is beneficial to improve the bonding ability of the coating and improve the structural stability of the battery. Specifically, the mass ratio of the binder to the flavonoid compound can be, but is not limited to, 0.01:1, 0.1:1, 0.3:1, 0.5:1, 0.8:1 or 1:1, etc. In one embodiment of the present application, the mass ratio of the binder to the flavonoid compound can be (0.01-0.5):1. In another embodiment of the present application, the mass ratio of the binder to the flavonoid compound can be (0.4-1):1.

[0042] In one embodiment of the present application, the coating 12 further includes an additive.

[0043] In one embodiment of the present application, the thickness of the coating 12 is 0.5 μm-3 μm. A suitable coating thickness can improve the structural stability of the diaphragm. Specifically, the coating thickness can be, but is not limited to, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm or 3 μm, etc. In one embodiment of the present application, the thickness of the coating can be 0.5 μm-2 μm. In another embodiment of the present application, the thickness of the coating can be 1.6 μm-3 μm.

[0044] In one embodiment of the present application, the coating surface density of the coating on the surface of the diaphragm is 0.05 g / m 2 -0.5g / m 2 The amount of metal ion deposition on the negative electrode can be reduced, the impedance of the battery can be reduced, and the capacity and cycle stability of the battery can be increased. Specifically, based on the mass of the flavonoid compound, the coating surface density of the coating on the surface of the diaphragm can be, but is not limited to, 0.05 g / m 2 , 0.1g / m 2 , 0.2g / m 2 , 0.3g / m 2 , 0.4g / m 2 or 0.5g / m 2In one embodiment of the present application, based on the mass of the flavonoid compound, the coating surface density of the coating on the surface of the diaphragm can be 0.05 g / m 2 -0.3g / m 2 In another embodiment of the present application, the coating surface density of the coating on the surface of the diaphragm can be 0.25 g / m 2 -0.5g / m 2 .

[0045] In one embodiment of the present application, in the diaphragm, the mass percentage of flavonoids is 1%-6%, and an appropriate amount of flavonoids can further alleviate the metal deposition phenomenon and improve the battery capacity and safety. Specifically, in the diaphragm, the mass percentage of flavonoids can be but not limited to 1%, 2%, 3%, 4%, 5% or 6%, etc. In one embodiment of the present application, in the diaphragm, the mass percentage of flavonoids can be 2%-3%, which can alleviate the metal deposition phenomenon while reducing the preparation cost of the diaphragm, which is beneficial to improving the safety and cycle stability of the battery. In another embodiment of the present application, in the diaphragm, the mass percentage of flavonoids can be 3%-6%.

[0046] The present application provides a method for preparing a diaphragm, comprising:

[0047] S101: dispersing the flavonoid compound in a solvent to obtain a coating slurry;

[0048] S102: coating the coating slurry on the base film, and obtaining a diaphragm after drying.

[0049] The preparation method provided in the present application is novel and has a simple preparation process. The prepared diaphragm can inhibit metal deposition and improve the safety and electrochemical performance of the battery.

[0050] In one embodiment of the present application, the solvent can promote the dispersion of flavonoids and improve the uniformity of the coating. Specifically, the solvent can be, but is not limited to, a non-polar organic solvent, and the non-polar organic solvent can be, but is not limited to, one or more of ether, dioxane, and benzene. In one embodiment of the present application, the solvent can be ether. In another embodiment of the present application, the solvent can be benzene.

[0051] In one embodiment of the present application, the drying temperature is 50°C-100°C, and the drying time is 1min-50min, which can improve the bonding ability between the coating and the base film and enhance the safety of the battery. Specifically, the drying temperature may be, but not limited to, 50°C, 60°C, 70°C, 80°C, 90°C or 100°C, etc.; the drying time may be, but not limited to, 1min, 5min, 10min, 20min, 30min, 40min or 50min, etc. In one embodiment of the present application, the drying temperature is 50°C-80°C, and the drying time is 1min-40min. In another embodiment of the present application, the drying temperature is 75°C-100°C, and the drying time is 30min-50min.

[0052] In one embodiment of the present application, the coating method may be scraping, spraying or roller coating.

[0053] Please participate Figure 2 , is a schematic diagram of the cross-sectional structure of a battery provided in one embodiment of the present application, wherein the battery 200 comprises a positive electrode sheet 20, a negative electrode sheet 30, a separator 100 and an electrolyte disposed between the positive electrode sheet 20 and the negative electrode sheet 30, and the separator comprises the separator described in any of the above embodiments or the separator obtained by the preparation method described in any of the above embodiments. The battery provided in the present application has excellent electrochemical performance, high battery capacity and safety, low battery impedance, long service life, and strong product competitiveness.

[0054] In one embodiment of the present application, the positive electrode plate includes a positive electrode current collector and a positive electrode active material layer disposed on the surface of the positive electrode current collector, and the positive electrode active material layer includes a positive electrode active material, which can improve the capacity and cycle stability of the battery. Specifically, the positive electrode active material may include, but is not limited to, one or more of lithium iron phosphate material, lithium iron manganese phosphate material, lithium manganate material, nickel cobalt manganese material, and nickel cobalt aluminum material. In one embodiment of the present application, the positive electrode active material includes lithium iron phosphate material. In this embodiment, the metal ions dissolved from the positive electrode plate include lithium ions and iron ions. The iron ions react with the flavonoid compounds in the diaphragm to prevent the iron ions from being deposited on the surface of the negative electrode plate. The lithium ions migrate through the diaphragm to improve the battery conductivity. In another embodiment of the present application, when the positive electrode active material includes lithium iron manganese phosphate material, the metal ions dissolved from the positive electrode plate include lithium ions, iron ions and manganese ions. The iron ions and manganese ions react with the flavonoid compounds in the diaphragm to prevent the iron ions and manganese ions from depositing on the surface of the negative electrode plate. The lithium ions migrate through the diaphragm to improve the battery conductivity.

[0055] In one embodiment of the present application, the positive electrode current collector may be, but is not limited to, at least one of copper, aluminum, nickel and stainless steel. In one embodiment of the present application, the positive electrode current collector may be aluminum foil.

[0056] In one embodiment of the present application, the positive electrode active material layer also includes a positive electrode conductor. The positive electrode conductor can increase the conductivity between active materials and improve electronic conductivity. Specifically, the positive electrode conductor may include but is not limited to at least one of graphite, carbon black, acetylene black and graphene. In one embodiment of the present application, the positive electrode conductor may be graphite. In another embodiment of the present application, the positive electrode conductor may be carbon black. In one embodiment of the present application, the positive electrode active material layer also includes a positive electrode binder, which can improve the binding ability of each component in the positive electrode active material layer and improve the binding ability between the positive electrode active material layer and the positive electrode current collector. Specifically, the positive electrode binder may be but is not limited to one or more of polyvinylidene fluoride, polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, polystyrene, polybutadiene, acrylic resin, epoxy resin, polyethylene oxide, sodium carboxymethyl cellulose and styrene butadiene latex. In one embodiment of the present application, the positive electrode binder may be polyvinylidene fluoride.

[0057] In one embodiment of the present application, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer disposed on the surface of the negative electrode current collector, and the negative electrode active material layer includes a negative electrode active material, which can accept lithium ions dissolved from the positive electrode plate to improve ion mobility. Specifically, the negative electrode active material may include but is not limited to one or more of soft carbon, hard carbon, artificial graphite, natural graphite, silicon, silicon oxides, silicon-carbon composites, lithium titanate, and metals that can form alloys with lithium. In one embodiment of the present application, the negative electrode active material may be soft carbon. In another embodiment of the present application, the negative electrode active material is lithium titanate.

[0058] In one embodiment of the present application, the negative electrode current collector may include, but is not limited to, at least one of copper, aluminum, nickel and stainless steel. In one embodiment of the present application, the negative electrode current collector may be copper foil.

[0059] In one embodiment of the present application, the negative electrode active material layer also includes a negative electrode binder, which can improve the binding ability of the components in the negative electrode active material layer and improve the binding ability between the negative electrode active material layer and the current collector. Specifically, the negative electrode binder can be, but is not limited to, one or more of polyvinylidene fluoride, polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, polystyrene, polybutadiene, acrylic resin, epoxy resin, polyethylene oxide, sodium carboxymethyl cellulose and styrene-butadiene latex. In one embodiment of the present application, the negative electrode binder can be polyvinylidene fluoride. In another embodiment of the present application, the negative electrode binder can be sodium carboxymethyl cellulose.

[0060] In one embodiment of the present application, the negative electrode active material layer also includes a negative electrode conductive agent and a thickener. The negative electrode conductive agent can increase the conductivity of the negative electrode material and improve the electronic conductivity. Specifically, the negative electrode conductive agent may include but is not limited to at least one of graphite, carbon black, acetylene black and graphene. In one embodiment of the present application, the negative electrode conductive agent may be graphite. In another embodiment of the present application, the negative electrode conductive agent may be carbon black.

[0061] In one embodiment of the present application, the electrolyte includes electrolyte salts, additives and electrolyte solvents, which are conducive to the construction of ion transmission channels in the battery and improve the electrochemical performance and safety performance of the battery. Specifically, the additives may include but are not limited to one or more of vinyl carbonate, triphenyl phosphate, methylene disulfonate and vinyl sulfate; the electrolyte solvent may include but is not limited to one or more of vinyl carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, polycarbonate, ethyl propionate and ethyl acetate. In one embodiment of the present application, the additive may be vinyl carbonate, which can promote the construction of the electrolyte membrane. In another embodiment of the present application, the electrolyte solvent may be vinyl carbonate.

[0062] In one embodiment of the present application, the electrolyte salt includes a lithium salt and a sodium salt. In one embodiment of the present application, when the battery is a lithium ion battery, the electrolyte salt may be a lithium salt.

[0063] In one embodiment of the present application, when the additive is vinylene carbonate, a new electrolyte membrane is formed to make up for the electrolyte membrane destroyed by the metal deposition phenomenon, thereby improving the capacity and safety of the battery. However, the large amount of vinylene carbonate used to form an electrolyte membrane with high density increases the impedance of the battery, which is not conducive to improving the electrochemical performance of the battery. The use of vinylene carbonate and the diaphragm provided by the present application can inhibit the deposition of metal ions on the negative electrode plate, avoid the reduction of battery impedance, and improve the power and cycle performance of the battery.

[0064] In one embodiment of the present application, the mass percentage of the additive in the electrolyte is 1%-5%, and the appropriate content of the additive can improve the electrochemical performance of the battery. Specifically, the mass percentage of the additive in the electrolyte can be but is not limited to 1%, 2%, 3%, 4% or 5%, etc. In one embodiment of the present application, the mass percentage of the additive in the electrolyte can be 1%-2%, which can further improve the capacity and cycle stability of the battery. In another embodiment of the present application, the mass percentage of the additive in the electrolyte can be 2%-5%.

[0065] In one embodiment of the present application, the additive includes vinylene carbonate, and the mass percentage a% of the flavonoid compound in the separator and the mass percentage b% of the vinylene carbonate in the electrolyte satisfy: a / 2+b≥3, and the calculation is performed based on the absolute value of the mass percentage a% of the flavonoid compound and the mass percentage b% of the vinylene carbonate. By controlling the mass of the additive (vinylene carbonate) and the flavonoid compound, it is beneficial to alleviate the metal deposition phenomenon, reduce the internal resistance of the battery, improve the high temperature service life, capacity and cycle performance of the battery, and improve the overall competitiveness of the battery.

[0066] The present application also provides an electrical device, which includes the battery described in any of the above embodiments. The electrical device provided in the present application has good cycle performance, high safety performance and long service life. Electrical equipment includes vehicles, electronic equipment, energy storage systems, etc., wherein the electronic equipment may include, for example, mobile phones, tablets, watches, VR glasses, etc. In one embodiment of the present application, the battery can be used in vehicles, which can improve the service life and cycle performance of the vehicle, improve the widespread application of new energy vehicles, and facilitate the construction of a green and environmentally friendly environment. In another embodiment of the present application, the battery can also be used in mobile phones, which can reduce the preparation cost of the battery and improve the safety of battery use. The above-mentioned battery of the present application can be arranged in the electrical equipment in the form of a single cell, a battery module, a battery pack, etc.

[0067] The effect of the technical solution of the present application is further illustrated below through specific examples.

[0068] Example 1

[0069] The flavonoid compound (anthocyanidin), the binder (styrene butadiene latex) and the ether solvent were mixed to obtain a coating slurry, the mass ratio of the flavonoid compound to the binder was 1:0.01, and the coating slurry was applied to a surface with a thickness of 12 μm and a surface density of 8 g / m 2 The polyethylene film was dried at 60° C. for 0.1 hour to obtain a separator; in the separator, the mass percentage of the flavonoid compound was 1%, and the coating surface density of the coating layer was 0.08 g / m 2 .

[0070] The positive electrode active material (lithium iron phosphate), the positive electrode conductive agent (acetylene black) and the positive electrode binder (polyvinylidene fluoride) are dissolved in N-methylpyrrolidone at a mass ratio of 96:2:2 to obtain a positive electrode slurry, and the positive electrode slurry is coated on a positive electrode collector (aluminum foil), and then dried, rolled and die-cut to obtain a positive electrode sheet;

[0071] The negative electrode active material (graphite after surface treatment), the negative electrode conductive agent (acetylene black), the negative electrode binder (styrene-butadiene rubber) and the thickener (sodium carboxymethyl cellulose) are dissolved in deionized water at a mass ratio of 95:2:2:1 to obtain a negative electrode slurry, which is then placed on a negative electrode current collector (copper foil), dried, rolled and die-cut to obtain a negative electrode sheet;

[0072] The positive electrode sheet, the separator, and the negative electrode sheet are stacked, baked, injected, soaked, formed, aged, exhausted, and divided to obtain a finished battery, wherein the electrolyte includes 1M LiPF 6 and solvent (EC:EMC in a volume ratio of 3:7).

[0073] Example 2

[0074] The difference from Example 1 is that the mass percentage of the flavonoid compound in the diaphragm is 2%, and the coating surface density of the coating is 0.16 g / m 2 .

[0075] Example 3

[0076] The difference from Example 1 is that the mass percentage of the flavonoid compound in the diaphragm is 3%, and the coating surface density of the coating is 0.24 g / m 2 .

[0077] Example 4

[0078] The difference from Example 1 is that the mass percentage of the flavonoid compound in the diaphragm is 6%, and the coating surface density of the coating layer is 0.48 g / m 2 .

[0079] Example 5

[0080] The difference from Example 1 is that the mass percentage of the flavonoid compound in the diaphragm is 7%, and the coating surface density of the coating is 0.6 g / m 2 .

[0081] Example 6

[0082] The difference from Example 1 is that the mass percentage of the flavonoid compound in the diaphragm is 0.5%, and the coating surface density of the coating is 0.04 g / m 2 .

[0083] Example 7

[0084] The difference from Example 1 is that the electrolyte includes 1% by mass of vinylene carbonate.

[0085] Example 8

[0086] The difference from Example 1 is that the electrolyte includes 2% by mass of vinylene carbonate.

[0087] Example 9

[0088] The difference from Example 1 is that the electrolyte includes 3% by mass of vinylene carbonate.

[0089] Example 10

[0090] The difference from Example 1 is that the mass percentage of the flavonoid compound in the separator is 2%, and the electrolyte includes 1 mass percentage of vinylene carbonate.

[0091] Embodiment 11

[0092] The difference from Example 1 is that the mass percentage of the flavonoid compound in the separator is 2%, and the electrolyte includes 2% by mass of vinylene carbonate.

[0093] Example 12

[0094] The difference from Example 1 is that the mass percentage of the flavonoid compound in the separator is 2%, and the electrolyte includes 3% by mass of vinylene carbonate.

[0095] Example 13

[0096] The difference from Example 1 is that the mass percentage of the flavonoid compound in the separator is 3%, and the electrolyte includes 1 mass percentage of vinylene carbonate.

[0097] Embodiment 14

[0098] The difference from Example 1 is that the mass percentage of the flavonoid compound in the separator is 3%, and the electrolyte includes 2% by mass of vinylene carbonate.

[0099] Embodiment 15

[0100] The difference from Example 1 is that the mass percentage of the flavonoid compound in the separator is 3%, and the electrolyte includes 3% by mass of vinylene carbonate.

[0101] Example 16

[0102] The difference from Example 1 is that the mass percentage of the flavonoid compound in the separator is 6%, and the electrolyte includes 1 mass percentage of vinylene carbonate.

[0103] Embodiment 17

[0104] The difference from Example 1 is that the mass percentage of the flavonoid compound in the separator is 6%, and the electrolyte includes 2 mass percentage of vinylene carbonate.

[0105] Embodiment 18

[0106] The difference from Example 1 is that the mass percentage of the flavonoid compound in the separator is 6%, and the electrolyte includes 3 mass% of vinylene carbonate.

[0107] Comparative Example 1

[0108] The difference from Example 1 is that the diaphragm is not provided with a coating.

[0109] Comparative Example 2

[0110] The difference from Example 1 is that the separator is not provided with a coating layer, and the electrolyte includes 5% by mass of vinylene carbonate.

[0111] Comparative Example 3

[0112] The difference from Example 1 is that the diaphragm does not contain flavonoids, and 6% by mass of Al is added. 2 O 3 .

[0113] Comparative Example 4

[0114] The difference from Example 1 is that the diaphragm does not contain flavonoids, and 6% by mass of Al is added. 2 O 3 , the electrolyte includes 3% by mass of vinylene carbonate.

[0115] Comparative Example 5

[0116] The difference from Example 1 is that the coating slurry does not include flavonoid compounds, and 6% by mass of EDTA is added.

[0117] Comparative Example 6

[0118] The difference from Example 1 is that the coating slurry does not include flavonoid compounds, 6% by mass of EDTA is added, and the electrolyte includes 3% by mass of vinylene carbonate.

[0119] Performance Testing

[0120] The batteries prepared in the above-mentioned Examples 1-18 and Comparative Examples 1-6 were tested for discharge capacity. The test process was as follows: charging at 0.05C for 2 hours at 45°C, switching to 0.2C constant current and constant voltage until the battery reached 3.8V (0.05C) and then discharging at 1 / 3 to 2V to measure the initial discharge capacity of the battery. The test results are shown in Table 1.

[0121] The batteries prepared in the above-mentioned embodiments 1-18 and comparative examples 1-6 were tested for their initial coulombic efficiency. The capacity of the battery when fully charged for the first time was C1, the capacity of the battery when divided for the first time was C2, and the calculation formula for the initial coulombic efficiency was C2 / C1×100%. The test results are shown in Table 1.

[0122] The internal resistance of the batteries prepared in the above-mentioned Examples 1-18 and Comparative Examples 1-6 was tested. The test process was as follows: the battery was adjusted to 50% SOC, and a stable voltage V1 was obtained after standing for 30 minutes; then the battery was discharged at a rate of 1.5C for 30 seconds to obtain a discharge voltage V2. The internal resistance of the battery was (V1-V2) / 1.5C. The test results are shown in Table 1.

[0123] The batteries prepared in the above-mentioned Examples 1-18 and Comparative Examples 1-6 were tested for their high temperature charge and discharge performance. The test process was as follows: the batteries were cycled at 60°C at a rate of 2C (3.8V to 2.0V range) for 200 cycles, and the capacity retention rate of each battery was counted. The test results are shown in Table 1.

[0124] The batteries prepared in the above-mentioned Examples 1-18 and Comparative Examples 1-6 were tested for iron content. The testing process was as follows: the batteries were disassembled to obtain the negative electrode plates, and the iron content was tested by inductively coupled plasma atomic emission spectroscopy (ICP). The test results are shown in Table 1.

[0125] Table 1 Test results

[0126] Battery capacity (Ah) Internal resistance(mΩ) Capacity retention rate (%) Iron deposition (ppm) Example 1 1.9 74.8 80.9 407 Example 2 1.9 74.5 81.3 365.8 Example 3 1.9 74.6 83.5 307.7 Example 4 1.89 74.8 84.1 196.9 Example 5 1.89 74.7 83.9 198 Example 6 1.9 74.8 79.5 487 Example 7 1.93 78.9 82.9 356.5 Example 8 1.93 84.2 83.4 216.5 Example 9 1.92 107.2 84 180.4 Example 10 1.93 78.8 83.2 324.6 Embodiment 11 1.93 84 83.9 195.9 Example 12 1.93 108.9 84.4 151.6 Example 13 1.93 79.1 83.3 237.1 Embodiment 14 1.93 84.1 84.2 182.5 Embodiment 15 1.93 108.7 84.7 128.9 Example 16 1.93 79.5 84.3 154.7 Embodiment 17 1.93 84.6 85.2 118.6 Embodiment 18 1.93 110.3 86.3 56.8 Comparative Example 1 1.88 74.5 71.2 581.2 Comparative Example 2 1.89 124.9 76 549.7 Comparative Example 3 1.86 88.5 73.7 551.6 Comparative Example 4 1.87 134.1 74.8 457.7 Comparative Example 5 1.90 99.5 77.7 221.4 Comparative Example 6 1.89 141.6 81.1 205.6

[0127] According to Examples 1-18 and Comparative Examples 1-6, the diaphragm provided by the present application has a low metal deposition content on the negative electrode during use, which improves the capacity retention rate of the battery. According to Example 1, Comparative Example 1 and Examples 2-4, it can be seen that the appropriate content of flavonoid compounds in the diaphragm coating is conducive to further alleviating the metal deposition phenomenon, preventing metal ions from depositing on the negative electrode to damage the electrolyte membrane, and is conducive to improving the cycle performance of the battery; According to Example 1 and Examples 5-18, it can be seen that the addition of vinyl carbonate to the electrolyte can also inhibit the deposition of metal ions and promote the formation of the electrolyte membrane. The appropriate content of vinyl carbonate can make the battery have high capacity, high first efficiency and low internal resistance; flavonoid compounds and vinyl carbonate have a synergistic effect, which can jointly alleviate the metal deposition phenomenon, improve the capacity and cycle performance of the battery, and reduce the battery impedance; the appropriate mass ratio of flavonoid compounds and vinyl carbonate can further improve the electrochemical performance of the battery; According to Example 1 and Comparative Examples 1-6, it can be seen that the diaphragm coating includes flavonoid compounds, compared with the traditional ceramic coating (Al 2 O 3) separator, which can effectively alleviate metal deposition and improve battery safety and cycle performance.

[0128] The above is a preferred embodiment of the present application, but it should not be understood as limiting the scope of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present application, and these improvements and modifications are also considered to be within the scope of protection of the present application.

Claims

1. A diaphragm, characterized in that: The diaphragm includes a base film and a coating layer disposed on at least one surface of the base film, wherein the coating layer includes a flavonoid compound.

2. The diaphragm according to claim 1, characterized in that Based on the mass of the flavonoid compound, the coating surface density of the coating on the surface of the diaphragm is 0.05 g / m 2 -0.5g / m 2 ; And / or in the diaphragm, the mass percentage of the flavonoid compound is 1%-6%.

3. The diaphragm according to claim 1, characterized in that The flavonoids include one or more of flavones, flavonols, dihydroflavones, dihydroflavonols, isoflavones, dihydroisoflavones, chalcones, dihydrochalcones, aurone, anthocyanidins, rutin, and catechins.

4. The diaphragm according to claim 1, characterized in that The flavonoids include anthocyanidins, and the structural formula of the anthocyanidins is Wherein, the R1 and the R2 are independently one of -H, -OH and -OCH3, the R3 is -H or a glycosyl, and the R4 is -OH or a glycosyl.

5. The diaphragm according to claim 1, characterized in that The material of the base film includes one or more of polyethylene, polypropylene, polyvinylidene fluoride and polyimide.

6. The diaphragm according to claim 1, characterized in that The coating further comprises a binder, wherein the binder comprises one or more of polyvinylidene fluoride, polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, polystyrene, polybutadiene, acrylic resin, epoxy resin, polyethylene oxide, sodium carboxymethyl cellulose and styrene-butadiene latex; and / or In the coating, the mass ratio of the binder to the flavonoid compound is (0.01-1):

1.

7. The diaphragm according to claim 1, characterized in that The coating has a thickness of 0.5 μm-3 μm.

8. A method for preparing a diaphragm according to any one of claims 1 to 7, characterized in that: include: dispersing the flavonoid compound in a solvent to obtain a coating slurry; The coating slurry is coated on a base film and dried to obtain a separator.

9. The preparation method according to claim 8, characterized in that: The solvent includes a non-polar organic solvent, and the non-polar organic solvent includes one or more of ether, dioxane, and benzene.

10. The preparation method according to claim 8, characterized in that: The drying temperature is 50° C.-100° C., and the drying time is 1 min.-50 min.

11. A battery, characterized in that: The battery comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte arranged between the positive electrode sheet and the negative electrode sheet, wherein the separator comprises the separator described in any one of claims 1 to 7 or the separator prepared by the preparation method described in any one of claims 8 to 10.

12. The battery according to claim 11, characterized in that The positive electrode plate includes a positive electrode active material, and the positive electrode active material includes one or more of a lithium iron phosphate material, a lithium iron manganese phosphate material, a lithium manganate material, a nickel cobalt manganese material, and a nickel cobalt aluminum material.

13. The battery according to claim 11, characterized in that The electrolyte comprises an electrolyte salt, an additive and an electrolyte solvent; The electrolyte solvent includes one or more of ethylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, polycarbonate, ethyl propionate and ethyl acetate; The additive includes one or more of vinylene carbonate, triphenyl phosphate, methylene methanedisulfonate and vinyl sulfate.

14. The battery according to claim 13, characterized in that The additive includes vinylene carbonate, and the mass percentage of the flavonoid compound in the separator is defined as a%, and the mass percentage of the vinylene carbonate in the electrolyte is defined as b%, satisfying a / 2+b≥3.

15. An electrical equipment, characterized in that: The electrical device comprises the battery according to any one of claims 11-14.